The Impact of Booklet-Based Interventions on PHBS Knowledge and Attitudes Among Household in Peniti Village - Peronika Sianturi; Selviana; Linda Suwarni (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: PHBS, or Clean and Healthy Living Behavior, is a set of actions individuals, families, and communities consciously undertake to enhance and preserve their health, as well as prevent diseases. To elevate public awareness and attitudes toward household PHBS, several strategies can be employed, including implementing health education programs. One such approach involves utilizing booklet media in the household PHBS education process to address community knowledge and attitudes. Objective: This research seeks to enhance community awareness and understanding of PHBS within household settings in Peniti Dalam Village, Segedong District. Method: This study employed a quasi-experimental design with a one-group pretest-posttest approach. The research was conducted in Peniti Dalam Village, Segedong District, from July to September 2024. The entire community of Peniti Dalam Village, Segedong District, served as the population for this research. A sample of 35 respondents was selected using purposive sampling techniques. Univariate and bivariate analyses, including the paired sample t-test, were utilized for data analysis. Result: The average attitude score increased from 1.40 in the pretest to 1.49 in the posttest, indicating a difference of 0.09. Univariate analysis revealed that, following PHBS education using booklet media, 48.6% of households demonstrated good to excellent knowledge, compared to the pre-education level. Similarly, the percentage of households with positive attitudes toward PHBS rose from 40% to 48.6% after receiving the booklet-based education. The results of the paired t test on the knowledge variable obtained a p value of 0.000 (> 0.05) and an attitude of 0.03 (> 0.05). This demonstrates that there is a significant difference between knowledge and attitudes before and after health education using booklet media. This suggests a significant association between attitudes, knowledge, and household PHBS education using booklet media. Conclusion: The findings indicate that household PHBS education through booklet media can successfully alter knowledge and attitudes. We recommend this technique for disseminating health information due to its demonstrated effectiveness in enhancing public awareness and attitudes, ultimately leading to a healthier society.